Particularism versus universalism in the Brazilian public administration literature - Candler, Gaylord George (2002)
The author draws on the Brazilian public administration literature to discuss the conflict between the need to remain open to lessons from elsewhere, while at the same time remaining grounded in a particular local context. The article begins by presenting calls by a number of Brazilian public administration scholars for what might be termed an "administrative particularism," or an assertion that universal lessons do not apply in the discipline. This is followed by a discussion of the challenges that these and other Brazilian public administration scholars identify. Further discussion will suggests these challenges, and many of the solutions most commonly offered for them, imply that, far from a uniquely Brazilian public administration, the country seeks to move closer to the model of public administration practiced elsewhere, especially in the developed world. - Reproduced.
Keywords: Public administration - Brazil; Public administration